Applying Antifragility in Design Principles for a Cyber Resilience Maturity Model - Botjes, Edzo A.; Huygh, Tim; Bollen, Laury; Helms, Remko W. (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
In an increasingly hyperconnected world rising uncertainty threatens both business continuity and society, prompting new regulatory responses from the EU and the US. Traditional, deterministic approaches to cyber resilience which focus merely on returning to a ‘status quo’ state after a disruption are no longer sufficient. Instead, organizations must evolve toward antifragility: the ability to thrive and exploit opportunities emerging from chaos. Drawing on an iterative design science research methodology this study proposes a theoretically grounded framework consisting of two design goals and twelve design principles to help organizations achieve antifragility within a cyber resilience context and guide the development of future cyber resilience maturity models.